Evaluation of Exercise Performance, Cardiac Function, and Quality of Life in Children After Liver Transplantation. Issue 7 (July 2016) - Vandekerckhove, Kristof; Coomans, Ilse; De Bruyne, Elke; De Groote, Katya; Panzer, Joseph; De Wolf, Daniel; Boone, Jan; De Bruyne, Ruth
Abstract : Background: In children, after having liver transplantation (LT), it is important to assess the quality of life (QOL). Physical fitness is an important determinant of QOL, and because cardiac function can influence exercise performance, it is the purpose of the present study to assess these factors. Methods: Children in stable follow-up for more than 6 months post-LT were invited to participate in a case control study. Patients underwent cardiopulmonary exercise testing and echocardiography to assess systolic and diastolic function, and left ventricular wall dimensions. Health-related QOL was evaluated using child- and adolescent-reported PedsQL questionnaire. Results: Twenty-eight of 31 included patients performed a maximal exercise test (15 boys, 11.6 ± 2.9 years, weight, 40.9 ± 13.1 kg; length, 148.6 ± 17.3 cm; body mass index, 17.6 ± 2.3). Liver transplantation patients had lower maximal oxygen consumption (VO2max /kg) (37.5 ± 9.3 mL/kg per minute vs 44.1 ± 8.8 mL/kg per minute), shorter exercise duration (9.3 ± 2.8 minutes vs 13.3 ± 3 minutes) and lower load (71 ± 14 vs 85 ± 20%). They reached the ventilatory anaerobic threshold earlier (81.4 ± 9.5 vs 88.3 ± 11.9%). Echocardiography demonstrated increased interventricular septal wall thickness (interventricular septum in diastole Z value, +0.45 ± 0.49, P < 0.001) and more diastolic dysfunction (lower E', Z value, −0.7 ± 1.02, P = 0.002, higher E/E' Z value, 0.64 ± 1.05. P = 0.005) but no relations with cardiopulmonary exercise testing. Health-related QOL showed lower overall, emotional, psychosocial, and school functioning scores. Children on antihypertensive medication had impaired physical functioning compared with other LT patients. Conclusions: Lower physical fitness level, more deconditioning and lower health-related QOL in children after LT emphasize the importance of exercise stimulation and fitness programs. Patients on antihypertensive medication seem to be the most vulnerable group suffering from decreased physical fitness. Abstract : Optimization of quality of life (QOL) and minimization of long-term complications, particularly cardiovascular diseases are major outcome measures in liver transplant programs. This is particularly relevant in children. The authors describe lower physical fitness level, more deconditioning and lower HR-QOL in this group, emphasizing the importance of exercise stimulation and fitness programs. Supplemental digital content is available in the text.